Comparative Analysis of Virulence and Toxin Expression of Vancomycin-Intermediate and Vancomycin-Sensitive Staphylococcus aureus Strains - Jin, Ye; Yu, Xiao; Zhang, Shuntian; Kong, Xiaoyang; Chen, Weiwei; Luo, Qixia; Zheng, Beiwen; Xiao, Yonghong (Frontiers in Microbiology, 2020)
Previous studies on vancomycin-intermediate Staphylococcus aureus (VISA) have been performed largely with respect to investigation of drug resistance, information regarding the of virulence evolution between VISA and VSSA requires further investigation. Here, we compared the virulence and toxin expression of VISA and VSSA strains by using a series of vancomycin-resistant induced S. aureus strains—SA0534, SA0534-V8, and SA0534-V16, and another two pair groups. In this study, we first used the mouse skin infection model to evaluate the invasive capacity of VISA strains. We found that mice infected with VISA had smaller abscess size, and persistent abscess was observed with VISA strains up to 9 days. Next, Infection with VISA strains produced lower mortality in a Galleria mellonella infection model (survival percent, ≥40% at 28 h) than infection with VSSA strains (survival percent, ≤3% at 28 h). In addition, we found that compared with VSSA, the ability of colonization in VISA strains were stronger. Furthermore, vitro experiments were performed to show the VISA strains are less virulent than VSSA strains, but showed better intracellular survival than VSSA. Finally, RNA-seq was used to find out the possible functions of virulence factors changed in VISA strains, demonstrating the significant changes in the expression of agr, hla, cap, spa, clfB, and sbi may lead to less platelet activation in VISA strains. Taken together, these findings highlight that virulence of VISA strains are relatively weaker than VSSA strains, but have stronger capacity to against destruction by the host innate immune system and colonize in the human host, thereby likely contributing to the promotion of persistent and chronic S. aureus infection instead of acute virulence.